Association of heart rate with heart failure outcomes and the effects of empagliflozin in patients with preserved ejection fraction – EMPEROR-Preserved trial. (3rd October 2022) - Boehm, M; Anker, S D; Mahfoud, F; Filippatos, G; Ferreira, J P; Pocock, S J; Brueckmann, M; Linetzky, B; Schueler, E; Wanner, C; Zannad, F; Packer, M; et al.
Abstract: Background and objective: High resting heart rate (HR) associates with cardiovascular death (CVD) and heart failure hospitalisation (HFH) in patients with reduced ejection fraction (HFrEF), but data are sparse in patients with preserved (HFpEF) or mildly reduced (HFmrEF) ejection fraction. Empagliflozin reduced the risk of CVD and HFH in HFpEF in the EMPEROR-Preserved trial. This study analyses the influence of HR on outcomes in patients with left ventricular ejection fraction (LVEF) >40% in EMPEROR-Preserved and evaluates the effects of empagliflozin across HR categories. Methods: Patients (n=5988) with HFpEF (LVEF >40%) were categorised to HR <70 beats per minute (bpm), 70–75 bpm and >75 bpm. The composite of CVD or HFH (primary outcome), first HFH, CVD, recurrent HFH and all-cause mortality were studied in the HR groups and in patients separated by sinus rhythm (SR) or atrial fibrillation (AF) and true HFpEF (EF ≥50%) or HFmrEF (EF 40–49%). Results: Empagliflozin did not influence HR over time. At HR >75 bpm, the primary outcome (hazard ratio: 1.31, 1.13–1.52, p=0.0003), time to first HFH (hazard ratio: 1.25, 1.04–1.49, p=0.02), recurrent HFH (hazard ratio: 1.29, 1.05–1.60, p=0.02), CVD (hazard ratio: 1.49, 1.21–1.84, p=0.0001) and all-cause mortality (hazard ratio: 1.49, 1.28–1.73, p<0.0001) were increased compared to HR of <70 bpm with HR 70–75 bpm showing intermediate results. The influence of HR on the primary outcome was only observed in SR (p trend=0.005), but not in AF (p trend=0.55). Patients with true HFpEF (≥50%) or HFmrEF (40–49%) showed similar effects. The treatment effects of empagliflozin to reduce the primary outcome, time to first HFH and recurrent HFH were not modified by HR. Conclusions: HR in SR, but not in AF, predicts heart failure outcomes in HFpEF and HFmrEF, but the effects of empagliflozin were not modified by HR. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boehringer Ingelheim & Eli Lilly and Company Diabetes Alliance